KETERKAITAN AKTIVITAS MATAHARI DENGAN SUHU PERMUKAAN LAUT ( SEA SURFACE TEMPERATURE/SST) DAN ENSO DI ATAS INDONESIA - Wilson Sinambela; Tiar Dani; Iyus E. Rusnadi (Jurnal Sains Dirgantara, 2007)
This paper present the relationships between long-term solar activities and sea surface temperature (SST) anomalies over Indonesian regions. Analysis on the relatioships between these parameters is carried out by using wavelet-base analysis techniques and correlation analysis. The wavalet Transform-base analysis (WWZ) for SST anomaly time series are gouped for overall Indonesian SST (SSTI), Western Indonesia SST (SST KIB), Middel Indonesian (SST KITeng) and Eastern Indonesian SST (SST KIT). And also grouped by season, dry season (JJA) and wet season (DJF) during the period of 1860-2005. The WWZ result for SST anomaly time series over Indonesia show some long period main signals with periods of 83 year, (50, 33, 25) year, (9-13) year which are suspected to be associated with solar activity sycles of 80-110 year (Gleissberg cycle), 50 year (interdecadal cycle), 22 year (cycle Hale) and 11-year of solar activity. There are also appear some signals with shorter periods of (3-7) year, (1.5-2.7) year, and (0.5-1) year which are suspected to be associated with ENSO, QBO, and seasonal / annual effects, respectively. From the result of long-term correlation analysis between solar activities with solar cycle length indicator and the 11 and 22 year running moving average Indonesian SST anomalies show good correlation for all data group. While the SST over KIT shows a negative correlation, but during of 1950-2005 shows s positive correlation.